2020
DOI: 10.1038/s41598-020-57815-z
|View full text |Cite
|
Sign up to set email alerts
|

Unique IL-13Rα2/STAT3 mediated IL-13 regulation detected in lung conventional dendritic cells, 24 h post viral vector vaccination

Abstract: This study demonstrates that 24 h following viral vector-based vaccination IL-13Rα2 functions as a master sensor on conventional dendritic cells (cDCs), abetted by high protein stability coupled with minimal mRNA expression, to rapidly regulate DC mediated IL-13 responses at the lung mucosae, unlike IL-13Rα1. Under low IL-13, IL-13Rα2 performs as a primary signalling receptor, whilst under high IL-13, acts to sequester IL-13 to maintain homeostasis, both in a STAT3-dependent manner. Likewise, we show that vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 59 publications
6
27
0
Order By: Relevance
“…In this study AddaVax was used with the SOSIP gp140 booster. However, taken together our recent findings 21 , 24 , 25 (S.Fig. 12 ), we find that selecting an adjuvant that can induce much lower ILC2-derived IL-13 may prove useful in inducing more robust/improved Env-specific immune outcomes with our SOSIP gp140 booster strategy in a clinical setting.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In this study AddaVax was used with the SOSIP gp140 booster. However, taken together our recent findings 21 , 24 , 25 (S.Fig. 12 ), we find that selecting an adjuvant that can induce much lower ILC2-derived IL-13 may prove useful in inducing more robust/improved Env-specific immune outcomes with our SOSIP gp140 booster strategy in a clinical setting.…”
Section: Discussionsupporting
confidence: 56%
“…When unravelling the immune mechanisms linked to our vaccines, we have shown that IL-4R antagonist adjuvanted vaccine induce significantly reduced ILC2-derived IL-13 at the vaccination site 24 h post-delivery compared to the control 17 , responsible for the observed immune outcomes 24,26 . Recently, using range of viral vector-based vaccines we have also demonstrated that ILC-derived IL-13 is the master regulator of different ILC subsets, as well as DC activity at the early stage of vaccination, shaping the downstream adaptive immune outcomes [17][18][19][20][21]23 . Specifically, although IL-13 is known to be detrimental for high avidity T cell induction 13,15,23 , low IL-13 at the vaccination site has shown to be crucial for effective antibody differentiation/ formation 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be the result of an alternative use of IL-13Ra2/STAT3 signaling rather IL-13Ra1/STAT6 in tAMs. Indeed, IL-13Ra2 has been shown to contribute to allergic asthma [ 40 ] and plays a unique role in the function of conventional pulmonary dendritic cells [ 41 ]. In contrast, although IL-33 influences polarization of alveolar macrophages [ 42 ], there is limited evidence for a role of IL-33 in the formation of giant cells, although it may be a decisive pro-inflammatory cytokine contributing to the pathology of Giant Cell Arteritis [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 can also bind to IL-13Rα1 of the type II IL-4 receptor complex, with low affinity (nM concentrations) and initiate signaling via the JAK/STAT6 pathway [ 8 ]. Furthermore, under low IL-13 conditions (pM concentrations), IL-13 is also thought to signal via the not well-characterized IL-13Rα2 pathway [ 13 ], involving STAT3 and activation of TGF-β1 [ 14 ]. Several studies have now shown that IL-13Rα2 can bind to IL-4Rα cytoplasmic tail and inhibit IL-4/IL-13 signaling via the IL-13Rα1/IL-4Rα type II complex and JAK/STAT6 [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%